Arachidonate lipoxygenases 5 is a novel prognostic biomarker and correlates with high tumor immune infiltration in low-grade glioma - Pan, Rui-han; Zhang, Xin; Chen, Zu-peng; Liu, Ya-jun (Frontiers in Genetics, 2023)
Objective: To investigate the prognostic value of arachidonate lipoxygenases 5 (ALOX5) expression and methylation, and explore the immune functions of ALOX5 expression in low-grade glioma (LGG). Materials and Methods: Using efficient bioinformatics approaches, the differential expression of ALOX5 and the association of its expression with clinicopathological characteristics were evaluated. Then, we analyzed the prognostic significance of ALOX5 expression and its methylation level followed by immune cell infiltration analysis. The functional enrichment analysis was conducted to determine the possible regulatory pathways of ALOX5 in LGG. Finally, the drug sensitivity analysis was performed to explore the correlation between ALOX5 expression and chemotherapeutic drugs. Results: ALOX5 mRNA expression was increased in LGG and its expression had a notable relation with age and subtype (P <0.05). The elevated mRNA level of ALOX5 could independently predict the disease-specific survival (DSS), overall survival (OS), and progression-free interval (PFI) (P <0.05). Besides, ALOX5 expression was negatively correlated with its methylation level and the ALOX5 hypomethylation led to a worse prognosis (P <0.05). The ALOX5 expression also showed a positive connection with immune cells, while LGG patients with higher immune cell infiltration had poor survival probability (P <0.05). Further, ALOX5 might be involved in immune- and inflammation-related pathways. Importantly, ALOX5 expression was negatively related to drug sensitivity. Conclusions: ALOX5 might be a promising biomarker, and it probably occupies a vital role in immune cell infiltration in LGG.